2008
DOI: 10.1176/ps.2008.59.9.1011
|View full text |Cite
|
Sign up to set email alerts
|

Housing for Persons With Serious Mental Illness: Consumer and Service Provider Preferences

Abstract: Mental illness symptoms may be a trigger for receiving an array of services for homeless women once they gain entrance into a service system. There was a negative association between symptoms of mental illness and use of behavioral health services among homeless mothers, which may be the result of the fear of child welfare service intervention and loss of child custody. This service distribution inequity among homeless women using mental health services deserves attention by policy makers, researchers, and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 18 publications
1
17
0
2
Order By: Relevance
“…Un dispositif d'hébergement pour les usagers, conceptualisé selon un continuum progressif d'encadrement (des ressources intermédiaires aux logements autonomes) a été graduellement introduit. Dans ce continuum, l'hébergement autonome avec soutien s'est progressivement imposé comme le modèle privilégié (Piat et al, 2008). L'approche Logement d'abord en représente un modèle clé (Tableau 1).…”
unclassified
“…Un dispositif d'hébergement pour les usagers, conceptualisé selon un continuum progressif d'encadrement (des ressources intermédiaires aux logements autonomes) a été graduellement introduit. Dans ce continuum, l'hébergement autonome avec soutien s'est progressivement imposé comme le modèle privilégié (Piat et al, 2008). L'approche Logement d'abord en représente un modèle clé (Tableau 1).…”
unclassified
“…An unintentional consequence of this transition, combined with other economic and housing-related factors, has been inadequate, inconsistent, or unstable housing for many individuals with mental illnesses. 481 Choice in housing is very important to consumers, with many consumers choosing more autonomous living situations when given the opportunity. 481 Piat and Bloom 481 asked consumers and case managers to rank their housing preferences on a list that ranged from one's own apartment to a hospital.…”
Section: Individuals Who Are Homeless or At Risk For Homelessnessmentioning
confidence: 99%
“…481 Choice in housing is very important to consumers, with many consumers choosing more autonomous living situations when given the opportunity. 481 Piat and Bloom 481 asked consumers and case managers to rank their housing preferences on a list that ranged from one's own apartment to a hospital. The authors found that most consumers preferred living in settings with more autonomy than their current living situations provided.…”
Section: Individuals Who Are Homeless or At Risk For Homelessnessmentioning
confidence: 99%
“…Overall, staff seem to value safety and support more (Piat 2008), whereas service users value independence and privacy. Obviously, a good solution to the dilemma of conflicting professional/ service user preference would be to have a range of accommodation and support options facilitating choice, but also providing support where needed.…”
Section: Accommodation and Service User Choicementioning
confidence: 99%